Development of recyclable Fibre Metal Laminates (FML), their mechanical characterization and FE modelling, aiming at structural application in aeronautics - Bassi Stefano (EDP Sciences, 2021)
This study concerns with the optimisation of a fibre-reinforced composite material ply book and application to an aeronautical component. The presented material solution is a recyclable FML (Fibre Metal Laminate). Recyclable and structural PMCs (Polymeric Matrix Composites) developed up-to now in ENEA had to be improved to satisfy the high-demanding fire characteristics requirements in aeronautics, particularly for the case considered in ongoing project FireMat (www.firemat.it), namely a turbine-bonnet production. FireMat project objective is the combination of weight reduction and fire resistance, maximizing the use C2C recyclable, secondary and biomass derived raw materials. Aluminium layers were introduced inside the lamination, to act as oxygen barriers and improve fire-retardancy. FML were obtained starting from a fire-retardant biobased resin, which was associated with aeronautical grade basalt-derived mineral fabric, processed in the form of a prepreg and then coupled with aluminium foils. FE modelling was based on performed mechanical characterization of the single layers and inter- layer adhesive strength of the ply stack: a composite sandwich structure (including aluminium honeycomb) was optimised.